The prediction of athletes performance in sprint event using cumulative distribution function / Masrurah Hussin & Mohammed Arief Badrul - Hussin, Masrurah; Badrul, Mohammed Arief (2019)
Sprint event is one of the well-known track and field event in the world. Olympic Games are held every four years with The Summer and Winter Games alternating but two years separated while four years for Asian Games. Sprint athletes from both games aiming to be crowned as the world's best. But there is a small chance for an athlete from specific event to break the current Asian and world record. Therefore, the purpose of this project is to determine the rate of occurrence of world record to be broken. In this project, the method that will be use is cumulative distribution function which is one of the theory for probability distribution and statistics. First of all, construction of cumulative distribution function is essential to model the probability for an athlete to race within a certain range of times. After the parameter values for the model been estimated, the technique from probability theory will be used to determine the chance for an athlete to be able to break the current Asian and world record. The present study, the result will obtain the probability of a new record for Olympic and Asian sprinter in each specific event and the frequency of Asian or world record will be broken. Hence, the performance of Olympic and Asian athletes in sprinting can be compared.